2001
DOI: 10.1067/maj.2001.120434
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in cardiovascular risk profile after large-volume lipoplasty: A 1-year follow-up study

Abstract: Should these results be confirmed in larger studies, lipoplasty may prove to be a valuable tool for reducing some of the co-morbid conditions associated with obesity. (Aesthetic Surg J 2001;21:527-531.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
1
9
0
3
Order By: Relevance
“…Others have shown a sustained weight reduction of 3 kg (18) in obese women at 6‐months following large‐volume lipectomy (>5,000 ml), and 4.6 kg (19) following small‐volume lipectomy at 6‐months, but the weight maintenance was by design. In another study, weight reduction after large‐volume liposuction remained at 4 months (20), and 1 year (21). However, patients underwent a larger volume of AT removal with or without ancillary procedures (abdominoplasty/body lift), the weight of skin removal was not reported, and again there was no control group.…”
Section: Discussionmentioning
confidence: 98%
“…Others have shown a sustained weight reduction of 3 kg (18) in obese women at 6‐months following large‐volume lipectomy (>5,000 ml), and 4.6 kg (19) following small‐volume lipectomy at 6‐months, but the weight maintenance was by design. In another study, weight reduction after large‐volume liposuction remained at 4 months (20), and 1 year (21). However, patients underwent a larger volume of AT removal with or without ancillary procedures (abdominoplasty/body lift), the weight of skin removal was not reported, and again there was no control group.…”
Section: Discussionmentioning
confidence: 98%
“…Giese et al [4,5] demonstrated a reduction in weight, body mass index (BMI), fasting insulin levels, and blood pressure in large-volume liposuction patients during a 1-year and 4-month study. Klein et al [6] presented a study of large-volume abdominal liposuction with 15 patients.…”
Section: Introductionmentioning
confidence: 98%
“…The superb work by Sharon Giesse and others has clearly shown that large liposuction can alter the postoperative metabolism in most patients [3,4]. Had the authors simply assessed the hemoglobin A1c level preoperatively in 296 patients, then again after 3 or 4 months, they could have answered the question once and for all.…”
mentioning
confidence: 99%
“…Everyone knows that obesity is associated with an altered metabolism, which includes type 2 diabetes. Whether the hypoglycemia occurs as a result of insufficient or partially ineffective insulin, an immune response to insulin, or hyperactive adipose tissue that soaks up the available insulin, the reduction of fat, by gastric bypass [1][2][3][4], serious dieting, or liposuction, reduces insulin needs substantially.…”
mentioning
confidence: 99%